"أثر المناخ التنظيمي على سلوك المواطنة التنظيمية للعاملين في المؤسسة دراسة حالة مؤسسة سونلغاز - بالوادي" - نوره, دقه; عبد الحميد, زوزو (جامعة الوادي - University of Eloued, 2023)
"تهدف هذه الدراسة إلى معرفة أثر المناخ التنظيمي بأبعاده (الهيكل التنظيمي، القيادة, نمط الاتصال، المشاركة في اتخاذ القرارات, الحوافز) في سلوك المواطنة التنظيمية بمؤسسة سونلغاز بالوادي. اعتمدنا في الدراسة على المنهج الوصفي التحليلي واستخدمنا كل من الاستبيان والمقابلة كأدوات لجمع المعلومات، تم توزيع الاستبيان على عينة عشوائية تمثلت في 30 موظف بالمؤسسة، وقد تم استخدام برنامج الحزمة الإحصائية لعلوم الاجتماعية (SPSS25) من أجل تحليل البيانات واختبار صحة الفرضيات. أهم النتائج التي توصلت إليها الدراسة: - ان مستوى المناخ التنظيمي في المؤسسة محل الدراسة متوسط؛ - ان مستوى سلوك المواطنة التنظيمية بأبعادها المختلفة لدى أفراد العينة مرتفع بالمؤسسة محل الدراسة؛ - توجد علاقة ارتباط طردية بين المناخ التنظيمي وسلوك المواطنة التنظيمية؛ - يساهم المناخ التنظيمي بأبعاده (الهيكل التنظيمي، القيادة، نمط الاتصال، مشاركة العاملين، الحوافز) في تفسير سلوك المواطنة التنظيمية بأبعادها (الإيثار، الكياسة، السلوك الحضاري، الروح الرياضية، وعي الضمير). " "This study aims to learn about the impact of the organizational climate in its dimensions (organizational structure, communication leadership, incentives, participation in decision-making in organizational citizenship behaviour at Sonlgas Valley. In the study, we relied on the analytical descriptive curriculum and used both the questionnaire and the interview as tools for gathering information. The questionnaire was distributed to a random sample of 30 employees of the institution. The Social Science Statistical Package Program (SPSS25) was used to analyze the data and test the validity of hypotheses. The study's main findings: - The level of organizational climate in the institution under consideration is average. - The level of organizational citizenship behaviour in its different dimensions to the members of the sample is high in the institution under consideration. - There is a correlation between the regulatory climate and the conduct of organizational citizenship. - The organizational climate in its dimensions (organizational structure, leadership, communication pattern, employee participation, incentives) contributes to the interpretation of organizational citizenship behaviour in its dimensions (altruism, civility, civilizational behaviour, sportsmanship, conscience.( "
Keywords: المناخ التنظيمي, الهيكل التنظيمي, القيادة, الاتصال, سلوك المواطنة التنظيمية.; organizational climate, organizational structure, leadership, communication, organizational citizenship behaviour.